(3JdNjU eYQaI GdJGHYjf ef GdKbGJs - (3eMeO Hf CMeO Hf YKeGf Hf bGjeGR GdPgHj, TeS GdOjf, CHh YHO Gddg,J (B748 (3g` s; (3GHf MjGf GdSHJjs
(3ChdgG (B:s
(3jHOC HJQLeI dEHQGgje Hf YHO GdQMef Hf Yha s
(3BNQgG (B:s
(3jfJgi HJQLeI CHj SHc Yf CHj gQjQI hYfg RjGO Hf SYO s
(3hgh JdNjU ef GdeLdO GdKGdK ef JGQjN GHf MjGf GdeYQha HGdKbGJ fSNI fajSI HNW GdPgHi GdPi dNU GdcJGHs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs